2018
DOI: 10.1111/anu.12838
|View full text |Cite
|
Sign up to set email alerts
|

Partial replacement of fishmeal by fermented soybean meal in diets for juvenile white shrimp (Litopenaeus vannamei)

Abstract: As an important feed ingredient, fermented soybean meal (FSM) has been widely used in aquatic animals due to its stable sources and reasonable price. Here, we evaluated the potential for replacement of fishmeal (FM) with FSM in diet of Litopenaeus vannamei. Five isonitrogenous (410 g/kg) and isolipidic (80 g/kg) diets were formulated: a control diet containing 320 g/kg FM and four experimental diets in which FM in control diet was replaced by FSM at 10 (FSM10%), 20 (FSM20%), 30 (FSM30%) and 40% (FSM40%). An 8-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
19
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 47 publications
4
19
1
Order By: Relevance
“…Qiu and Davis reported that plant‐based spray‐dried fermented biomass can replace up to 50% of FM, which is in line with the results of the present study. In this study, FE and PER showed the same trends as WG and SGR which is in agreement with the results of Shao et al . Survivability was not affected by the dietary treatments indicating that whiteleg shrimps have resistance to increasing BPC levels in the diets which is line with the findings of Qiu and Davis .…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…Qiu and Davis reported that plant‐based spray‐dried fermented biomass can replace up to 50% of FM, which is in line with the results of the present study. In this study, FE and PER showed the same trends as WG and SGR which is in agreement with the results of Shao et al . Survivability was not affected by the dietary treatments indicating that whiteleg shrimps have resistance to increasing BPC levels in the diets which is line with the findings of Qiu and Davis .…”
Section: Resultssupporting
confidence: 92%
“…reported that 50% FM can be replaced in the diet of white shrimp using rice protein concentrate. Recently, Shao et al . found that 20% of FM could be successfully replaced by fermented SBM in the diet of white shrimp which is lower than that of the present study.…”
Section: Resultscontrasting
confidence: 84%
See 2 more Smart Citations
“…The scenario of diminished availability and escalating price of fishmeal in recent years prompted the researchers to substitute its considerable quantity by using various alternatives. One among them is fermented oilseed meals/cakes (Shiu et al, 2015;Sun et al, 2015;Sharawy et al, 2016;Jannathulla et al, , 2018a. Though fermented plant proteins are being used as a potential substitute of fishmeal in shrimp feed, its relationship on digestive enzymes and their distribution pattern in P. vannamei is scarce.…”
Section: Introductionmentioning
confidence: 99%